2017
DOI: 10.1136/bmjspcare-2016-001286
|View full text |Cite
|
Sign up to set email alerts
|

Should heart failure be regarded as a terminal illness requiring palliative care? A study of heart failure patients’, carers’ and clinicians’ understanding of heart failure prognosis and its management

Abstract: This is the first study exploring the experiences of prognostic communication at all stages of HF. Findings raise questions regarding the pragmatic utility of the concept of HF as a terminal illness and have implications for future HF care pathway development. Findings support the incorporation of a problem-based approach to management, which recognises the importance of everyday functioning for patients and carers as well as the opportunity for ACP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This may be a phenomenon that is unique to people who experience intermittent decline. Our findings corroborate prior studies; in a study of older adults with advanced heart failure, Klindworth and colleagues found that older patients do not perceive heart failure as a life‐limiting illness . In a longitudinal study of patients with advanced chronic obstructive pulmonary disease, an advanced illness with a similar illness trajectory to heart failure, Pinnock and colleagues found that patients reported having been ‘restored to normal and the threat had receded’ following an exacerbation .…”
Section: Discussionsupporting
confidence: 90%
“…This may be a phenomenon that is unique to people who experience intermittent decline. Our findings corroborate prior studies; in a study of older adults with advanced heart failure, Klindworth and colleagues found that older patients do not perceive heart failure as a life‐limiting illness . In a longitudinal study of patients with advanced chronic obstructive pulmonary disease, an advanced illness with a similar illness trajectory to heart failure, Pinnock and colleagues found that patients reported having been ‘restored to normal and the threat had receded’ following an exacerbation .…”
Section: Discussionsupporting
confidence: 90%
“…In heart failure, the trajectory of each patient is different. Stocker et al . showed that the majority of patients with heart failure reject the idea of heart failure as a terminal disease and prefer to focus on day‐to‐day management and maintenance, despite obvious deterioration in disease stage and needs over time.…”
Section: Management Strategies For Patients With Advanced Heart Failurementioning
confidence: 99%
“…In heart failure, the trajectory of each patient is different. Stocker et al 265 showed that the majority of patients with heart failure reject the idea of heart failure as a terminal disease and prefer to focus on day-to-day management and maintenance, despite obvious deterioration in disease stage and needs over time. Common expectations pre-and post-heart transplant or MCS and potential complications should be discussed with patients and their caregivers, ideally, during the assessment and evaluation period for advanced heart failure therapies.…”
Section: Palliative Care Of Patients With Advanced Heart Failurementioning
confidence: 99%
“…Study designs assessing patients’ experiences indirectly that is, expert opinion, routine data that was not obtained from patients directly, or came from health professionals, will not be eligible for inclusion. On the other hand, since informal caregivers play a significant role in shaping patients’ experiences of healthcare services, studies that report patient experiences from the perspective of a patient’s close social network will be eligible for inclusion—especially towards end of life and when patients are unable to self-report their experiences 26…”
Section: Methods and Analysismentioning
confidence: 99%